An exploration of Dark Romanticism in Poe’s Gothic Fiction: a journey into the conscious and subconscious mind - Ahmed, Marjiya Baktyer (BRAC University, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2018.